Pengaruh Penggunaan Aplikasi Canva Terhadap Motivasi Dan Hasil Belajar Peserta Didik Pada Mata Pelajaran Teknologi Infomatika (TIK) Di SMAS Saidiyah Arusbaya Bangkalan - Hidayat, Dwi Fachmi Arif; Silver, Soesiana Tri Eka; Hanifah, Sri Yuni (Peneliti.net, 2024)
In the formulation of the problem in this research, is there an influence of using the Canva application learning media on the motivation and learning outcomes of SMAS Saidiyah Arusbaya Bangkalan students. The aim of the research is to see how the use of teaching materials in the Canva application influences the motivation and learning outcomes of SMAS Saidiyah Arusbaya Bangkalan students. The approach used is quantitative with data collection methods and data analysis using statistics. The calculation results show that rcount > rtable, so the hypothesis is accepted and the level of correlation coefficient is a high level of relationship. The Canva application variable in this study contributed to learning outcomes by 53%. Meanwhile, when testing the hypothesis using the multiple correlation formula, the results obtained were rcount 0.79 which was greater than rtable 0.344, Fcount 28.41 and Ftable 4.45. From the calculation results of the product moment correlation formula, it shows that rcount > rtable. So it can be concluded that there is an influence between the use of the Canva application and learning motivation and learning outcomes of class XI students at SMAS Saidiyah Arusbaya Bangkalan.